1998
DOI: 10.1117/12.316917
|View full text |Cite
|
Sign up to set email alerts
|

<title>Active composite materials as sensing elements for fiber-reinforced smart composite structures</title>

Abstract: Polymer based piezoelectric composite materials can be readily integrated within laminated composite structures to provide sensing and actuating capabilities. In this study composite films of ferroelectric ceramic/polymer materials have been developed and characterized as in-situ multi purpose sensing elements for the nondestructive monitoring of fiber reinforced composites. In this paper the response of embedded composite films to simulated acoustic emission signals will be presented and discussed.Results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Many researchers have demonstrated that new features may be induced by combining two or more materials in a controlled ratio which is known as the composite structures process, which has recently become an interesting topic of research [1][2][3][4]. Composites have been used in a variety of applications including sensors, electrodes, photocatalysts, fuel cells, non-volatile magnetic memories, and data storage device magnetic heads [5][6][7][8]. Zinc oxide (ZnO) nanoparticles have attracted a lot of attention because of their good performance in optics, electronics, and photonics fields [9].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have demonstrated that new features may be induced by combining two or more materials in a controlled ratio which is known as the composite structures process, which has recently become an interesting topic of research [1][2][3][4]. Composites have been used in a variety of applications including sensors, electrodes, photocatalysts, fuel cells, non-volatile magnetic memories, and data storage device magnetic heads [5][6][7][8]. Zinc oxide (ZnO) nanoparticles have attracted a lot of attention because of their good performance in optics, electronics, and photonics fields [9].…”
Section: Introductionmentioning
confidence: 99%
“…Moetakef, Joshi, and Lawrence (1996) performed finite-element modeling and experimental study of elastic waves generation through equally spaced piezoceramic wafers. Blanas et al (1997Blanas et al ( , 1998 studied the use of active composites sensors for acoustic-emission health monitoring. Liang et al (1996) developed an impedance method for dynamic analysis of active material systems.…”
Section: Introductionmentioning
confidence: 99%
“…This approach seemed to offer better resolution to detect high-frequency shifts due to transverse-crack damage. Blanas et al (1998) studied the use of composites active sensors for acoustic-emission health monitoring. Kawiecki (1998) demonstrated experimentally the feasibility of nondestructive damage detection by an array of piezotransducers (25-mm square, 025 mm thick) bonded to the surface of four types of structures: aluminum beam; aluminum plate; concrete beam; concrete block.…”
Section: Wave Propagation Methodologiesmentioning
confidence: 99%